MEMBICARAKAN ALLAH DENGAN MENGGUNAKAN VIA ANALOGIAM - Oktovianus Naif (Program Studi Filsafat Universitas Katolik Widya Mandira Kupang, 2017)
Since the beginning of the philosophical or theological discourse about God, there has been a problem of validity of a proposition about God. God is unlimited and human faculty is limited, so God in Him Self can not be totally comprehended by human intellect. Based on this concept Lateran Council explained that “inter creatorem et creaturam non potest (tanta) similitude notari, quin inter eos maior sit dissimilitude notanda”. How can we think and talk about God while at the same time respecting God’s mystery? Analogia entis would be a helpful solution in a discourse and proclamation about God.